Indonesian students’ reading literacy ability in the cooperative integrated reading and composition learning: A meta-analysis - Muhammad Fuad; Edi Suyanto; Ulul Azmi Muhammad; Suparman Suparman (Institute of Advanced Engineering and Science, 2023)
A few of meta-analysis studies regarding the intervention of cooperative learning have been conducted. However, it has not been performed on the studies related to the intervention of cooperative integrated reading and composition (CIRC) learning for Indonesian students’ reading literacy. This study aims to approximate and examine the effect of CIRC learning on students’ reading literacy ability across group size of intervention, educational level, and geographical location. A meta-analysis was performed to conduct this study. The search of document using the database of Google Scholar found 97 documents. The selection of document established 10 documents published from 2015–2021 consisting of one conference paper and nine journal articles. Hedges’ equation was employed to measure the effect size. The data analysis used the Z test and Q Cochrane test. The results revealed that the CIRC learning had a strong positive effect (g=2.041; p<0.05) on students’ reading literacy ability. It indicates that the CIRC learning is effective for enhancing students’ reading literacy ability. Furthermore, some moderating factors such as group size of intervention, educational level, and geographical location did not affect students’ heterogeneous reading literacy ability. This study suggests language teachers to use the CIRC learning in enhancing students’ reading literacy ability.